KARAKTERISTIK STRUKTUR KOMUNITAS MAKROZOOBENTOS DI PERAIRAN EKOSISTEM MANGROVE GILI LAWANG, LOMBOK TIMUR - Niechi Valentino; Sitti Latifah; Budhy Setiawan; Eni Hidayati; Zata Yumni Awanis; Hayati Hayati (Forestry Study Program University Of Mataram, 2022)
The role of the mangrove ecosystem as an ecological link through high productivity compared to other ecosystems has had a major impact on the existence of the mangrove ecosystem distribution. This study aims to find out the type of organic ingredient content and abundance of macrozoobenthos and find out the relationship of organic ingredient content to the abundance of macrozoobenthos. The research was carried out in November 2021 using a purposive sampling technique method with a total of 5 stations. The samples taken were the sediments substrate and macrozoobenthos. The results shown that the organic content is dominated by saturated textures, muddy sand textures and saturated clay textures with an average organic content ranging from 1.24% - 1.90%. There were 15 types of macrozoobenthos found and dominated by the Gastropod class with an average abundance of macrozoobenthos ranging from 202 ind/m2 - 525 ind/m2. The types of macrozoobenthos found were Nassarius distortus, Anadara sp, Mesodesma sp, Mytillus sp, Donax sp, Abra soyoae, Cerithideopsilla djadjariensis, Telescopium telescopium, Cassidula nucleus, Cassidula angulifera, Litttoridina sp., Potamopyrgus sp., Melanoides sp., Battilaria zonalis dan Lumbriculus sp. The effect of organic matter content on the abundance of macrozoobenthos by 10.7% and 89.3% was more influenced by physic-chemical factors in Gili Lawang waters.